Molecular structure, Spectroscopy, and HOMO-LUMO of Ferrocene by quantum computing methods - Kedadra, Abdellatif; Lanez Touhami (University Of Eloued جامعة الوادي, 2020)
The main objective of this work is the application of different molecular modeling bases to predict the chemical reactivities and biological activities expected in this molecule. The structure of Ferrocene was optimized with the Gaussian 09 software by the DFT / B3LYP method and the bases set LanL2DZ. the efficiency of the bioinformatic methods used in the calculations of geometric parameters can be evaluated by comparing the results obtained with the experimental values (X-ray). the FT-IR, UV-VIS spectra theoretically predicted. The H1 and C13 NMR spectra were calculated by the gauge independent atomic orbital method (GIAO). A study of electronic properties, such as HOMO and LUMO energies, was performed using a time-dependent DFT (TD-DFT) approach.
Intervention
Keywords: N; N-dimethyl ferrocenyl methyl amin; molecular modeling; DFT